Effective temperature and universal conductivity scaling in organic semiconductors - Abdalla, Hassan; Ruit, Kevin van de; Kemerink, Martijn (Scientific reports, 2015)
We investigate the scalability of the temperature- and electric field-dependence of the conductivity of disordered organic semiconductors to ‘universal’ curves by two different but commonly employed methods; by so-called universal scaling and by using the effective temperature concept. Experimentally both scaling methods were found to be equally applicable to the out-of-plane charge transport in PEDOT:PSS thin films of various compositions. Both methods are shown to be equivalent in terms of functional dependence and to have identical limiting behavior. The experimentally observed scaling behavior can be reproduced by a numerical nearest-neighbor hopping model, accounting for the Coulomb interaction, the high charge carrier concentration and the energetic disorder. The underlying physics can be captured in a simple empirical model, describing the effective temperature of the charge carrier distribution as the outcome of a heat balance between Joule heating and (effective) temperature-dependent energy loss to the lattice.
Gesehen am 05.12.2019